Addressing food and nutritional insecurity in Bahia municipalities in the context of the COVID-19 pandemic - Jerusa da Mota Santana; Valterlinda Alves de Oliveira Queiroz; Caroline Nascimento dos Anjos; Patrícia Rocha de Freitas; Dejanira Alves de Souza; Nedja Silva dos Santos Fonseca; Sandra Maria Chaves dos Santos (Demetra, 2022)
Introduction: Covid-19 pandemic has made it possible to worsen the situation of food and nutritional insecurity (FNI) in the population. Objective: To analyze the main institutional strategies for coping with FNI in the context of the Covid-19 pandemic in Bahian municipalities. Methods: This is an ecological study conducted from March to May 2020 in 44 municipalities in Bahia. The information was collected through consultations with the Official Gazette (OG) of the municipalities, with a survey of the strategies adopted to cope with FNI. The strategies identified were classified into the dimensions: income and living conditions; health, nutrition, and access to health services; food production and availability; access to adequate and healthy food and education. Results:  The main strategies for coping with FNI adopted were the dimension "income and living conditions" – with the provision of tax incentives (45.5%); the dimension "access to adequate and healthy food" – with strategies for distributing food or food cards to students enrolled in schools (38.6%) and distribution of basic food basket (34.1%). Conclusion: This study revealed low coverage of the strategies adopted by Bahian municipal executives to cope with FNI during the Covid-19 pandemic. The study highlights the need for greater social protection through government actions. It is essential that short-, medium- and long-term intersectoral measures be taken to serve, primarily, the most vulnerable populations in order to mitigate the social and economic impacts during and after the pandemic.